PENGARUH IMPLEMENTASI KEBIJAKAN REMUNERASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KARAWANG PROVINSI JAWA BARAT - Rohayati, Yeti (Institut Pemerintahan Dalam Negeri, 2019)
This research was conducted with the aim of knowing and analyzing the effect of policy implementation and motivation on the performance of the financial management and assets of the Karawang district. The independent variables are policy implementation (X1) and motivation (X2) as exogenous variables, and as endogenous variables are performance (Y). This research uses descriptive analysis method with the type of research survey research. The population was 127 pegwai while 56 people were sampled. Data collection using questionnaires as the main instrument, while for secondary data through interviews, and tracking through applicable regulations, analysis using quantitative techniques with descriptive statistics, and path analysis with the help of SPSS version 23 for Windows and Macro Minitab for Windows versions 17.0. Based on the analysis of quantitative data gives the results that the direct and indirect effects of policy implementation (X1) on the performance of 50.26%, and the direct and indirect influence of motivation (X2) on the performance of 29.39%, with a large effect of simultaneous implementation and motivation for the performance of employees of the financial management agency and regional assets of Karawang Regency is 79.65% (strong influence category). Meanwhile, other variables that affect the performance but not examined are 20.35%.